Profitability and resource use efficiency of different farming systems in inland salt-affected areas of Haryana - Mir, Shakir Ahmad; P.S., Ananthan; Qureshi, Neha wajahat; Argade, Shivaji D.; Krishnan, Sreedharan; Mukhopadhyay, Raj; Gul, Shahid; Majid Bhat, Naila (Journal of Indian Fisheries Association, 2023)
The current study has been undertaken to assess the profitability and efficiency of different farming systems in inland salt-affected areas of Haryana. Three different categories of farmers, which include shrimp farmers, proximal agriculture farmers, and distal agriculture farmers, were taken for this study. A total of 90 farmers were selected from the Rohtak district of Haryana, with 30 farmers from each category through purposive snowball sampling, and the data was collected using a structured interview schedule. Data was analysed with various statistical and econometric tools, viz., B-C ratio, Cobb-Douglas production function, and Data Envelopment Analysis (DEA). The results of the B-C ratio revealed that all the culture systems were profitable. However, the benefits were less for proximal agriculture farmers because of the reduction in production from shrimp farming in the adjacent areas. Feed cost had the higher share in total cost, with 64% for shrimp farming, while labour cost was dominant for agriculture farming. The estimated technical efficiency using DEA shows that distal farmers were more efficient (0.88) than shrimp farmers (0.80) and proximal farmers (0.69). Similarly, distal farmers were more cost-efficient (0.72) than shrimp farmers (0.63) and proximal farmers (0.59). The allocative efficiency was higher for proximal farmers (0.87), followed by shrimp farmers (0.84), while distal farmers had less allocative efficiency (0.68), and it indicated that the same level of output using the combination of inputs corresponds to the minimum cost of production. In order to reduce the cost of production, farmers are advised to acquire knowledge and managerial skills on the efficient use of farm inputs such as seed, feed, chemicals/medicines, and labour. The scientific mix of cultivable species, stocking density and proper combination of crops for the efficient use of resources, availability of feed mills in the nearby areas, adopting best management practices (BMPs) and good aquaculture practices (GAPs), scientific crop management strategies and use of eco-friendly technologies are probable ways to reduce the cost of production. Also, the government should put a checkmark on the effluent discharge from the shrimp farms and provide them with facilities for the effluent treatment on a payment basis.